7
$\begingroup$

$\mathbf {The \ Problem \ is}:$ If $A$ and $B$ be two $n\times n$ square matrix such that $A^2=A$ and $B^2=B,$ then show that $r(A-B)=r(A-AB)+r(AB-B)$ where $r(A)$ denotes rank of the square matrix $A.$

$\mathbf {My \ approach} :$ Actually I have tried that, from the two equations, $A(A-B)=(A-AB)$ and $(A-B)B=(AB-B)$, we have $r(A-AB)+r(AB-B) \leq r(A)+r(B)$ and again $A(AB-B)=0$ and $(A-AB)B=0$, then $r(A)+r(AB-B)\leq n$ and $r(B)+(A-AB)B\leq n$, but I can't draw any further conclusion to show that $r(A-AB)+r(AB-B) \leq r(A-B)$ .

And the other side is obvious by the rank-inequality $r(P+Q)\leq r(P)+r(Q).$

A small hint is warmly appreciated .

$\endgroup$
4
  • $\begingroup$ A quicker proof of the equality you attained: $$ r(A-B) = r([A - AB] + [AB - B]) \leq r(A - AB) + r(AB - B). $$ $\endgroup$ Jan 19, 2020 at 15:33
  • $\begingroup$ For the other direction, it suffices to show that $(A - AB),(AB - B)$ have trivially-intersecting row-spaces and columns spaces (which leads to a quick proof), but that might be a bit too strong a tool for this problem. $\endgroup$ Jan 19, 2020 at 15:35
  • $\begingroup$ I suspect that we might be able to come up with an elegant proof starting with $A - AB = (I - A)B$, $AB - B = A(I - B)$ and using the fact that $\ker(I - A) = \operatorname{im}(A)$. $\endgroup$ Jan 19, 2020 at 17:45
  • $\begingroup$ @Omnomnomnom,Sir,I was also thinking about this part, by using the fact that the vector space $V$ is the direct sum of the eigenspaces of the matrices $A$ and $B$ corresponding to the eigenvalues $0$ and $1$ respectively. But, I couldn't get further. $\endgroup$ Jan 19, 2020 at 21:21

2 Answers 2

2
+50
$\begingroup$

We want to show that $$ r(A-B) = r(A - AB) + r(AB - B). $$

By the claim proven below, it suffices to show that $A - AB$, $AB - B$ have trivially intersecting row-spaces and trivially intersecting kernels.

To show that the row-spaces intersect trivially, note that $$ \operatorname{im}(A - AB)^T = \operatorname{im}((I - B)^TA^T) \subset \operatorname{im}(I-B)^T,\\ \operatorname{im}(AB - B)^T = \operatorname{im}(B^T(I - A^T)) \subset \operatorname{im}(B)^T.\\ $$ However, we have $\operatorname{im}(B)^T \cap \operatorname{im}(I-B)^T = \{0\}$. To see this: if $x$ is in the first space, then $(I - B^T)x = 0$ which means that $B^Tx = x$. If $x$ is in the second space, then $B^Tx = 0$. For both to be true, we must have $x = 0$.

We now show that the kernels intersect trivially. Suppose that $x \in \ker(A-B)$, i.e. $(A-B)x = 0$. This can be rewritten as $$ (A - B)x = 0 \implies Ax - Bx = 0 \implies Ax = Bx. $$ It follows that $$ (A - AB)x = Ax - A(Bx) = Ax - A(Ax) = (Ax - A^2)x = 0. $$ Similarly, $$ (AB - B)x = A(Bx) - (Bx) = A(Ax) - (Ax) = (A^2 - A)x = 0. $$ So, $x \in \ker(A-B)$ implies that $x \in \ker(A - AB)$ and $x \in \ker(AB - B)$. The conclusion follows.


Claim: given $P,Q$ with $\operatorname{im}(P^T)\cap \operatorname{im}(Q^T) = \{0\}$, we have $$ r(P + Q) = r(P) + r(Q) \iff \ker(P + Q) = \ker(P) \cap \ker(Q). $$

Proof: $$ \ker(P + Q) = \ker(P) \cap \ker(Q) \iff\\ \operatorname{im}(P^T + Q^T) = \operatorname{im}(P^T) + \operatorname{im}(Q^T) \iff\\ \dim \operatorname{im}(P^T + Q^T) = \dim \operatorname{im}(P^T) + \dim \operatorname{im}(Q^T) - \dim[\operatorname{im}(P^T) \cap \operatorname{im}(Q^T)] \iff\\ \dim \operatorname{im}(P^T + Q^T) = \dim \operatorname{im}(P^T) + \dim \operatorname{im}(Q^T) \implies\\ r(P + Q) = r(P) + r(Q). $$

$\endgroup$
9
  • $\begingroup$ Can you explain "By the rank-nullity theorem...". By applying the rank-nullity theorem to which operators exactly? $\endgroup$ Jan 19, 2020 at 16:07
  • $\begingroup$ @punctureddusk to $A-B$. My justification was in order for the rank of $A-B$ to be as large as possible, its kernel must be as small as possible. Now that I reread it though, I see that's too informal. I do think that it is true that $$ r(P+Q) = r(P) + r(Q) \iff \ker(P+Q) = \ker(P) + \ker(Q) $$ though the proof eludes me at the moment $\endgroup$ Jan 19, 2020 at 16:20
  • $\begingroup$ @punctureddusk fixed my answer. Unfortunately, now it's not as short as I would have hoped. $\endgroup$ Jan 19, 2020 at 16:41
  • $\begingroup$ Can you explain some more the first equivalence in the proof? I'm sorry, this might just me being away from linear algebra for too long. $\endgroup$ Jan 19, 2020 at 16:53
  • $\begingroup$ @punctureddusk for subspaces $U$ and $V$, $(U \cap V)^\perp = U^\perp + V^\perp$, where $U^\perp$ is the orthogonal complement of $U$. $\endgroup$ Jan 19, 2020 at 16:55
2
$\begingroup$

Let $F$ be the underlying field, $V=F^n,\,A'=I-A$ and $B'=I-B$. Then $A'$ and $B'$ are also projectors and $AA'=A'A=BB'=B'B=0$. We have two observations:

  1. $r(AB')+r(A'B)=r(AB'-A'B)$:
    • Since $AB'V\cap A'BV\subseteq AV\cap A'V=0$, we have $AB'V\cap A'BV=0$. Hence \begin{aligned} r(AB')+r(A'B)&=\dim(AB'V)+\dim(A'BV)\\ &=\dim(AB'V)+\dim(A'BV)-\dim(AB'V\cap A'BV)\\ &=\dim(AB'V+A'BV). \end{aligned}
    • For any $x,y\in V$, we have $AB'x+A'By=(AB'-A'B)(B'x-By)$. Hence $AB'V+A'BV\subseteq (AB'-A'B)V$ and $$ \dim(AB'V+A'BV) \le\dim\left((AB'-A'B)V\right) =r(AB'-A'B) \le r(AB')+r(A'B). $$
  2. $r(AB'-A'B)=r(A-B)$: by rank-nullity thm, it suffices to show that $\ker(AB'-A'B)=\ker(A-B)$:
    • Suppose $(AB'-A'B)x=0$. Left-multiply both sides by $A$, we get $AB'x=0$. Subtract this equation from the previous one, we obtain $A'Bx=0$ too. Now $AB'x=0$ and $A'Bx=0$ imply that $Ax=ABx$ and $Bx=ABx$ respectively. Hence $(A-B)x=0$.
    • Conversely, suppose $(A-B)x=0$. Then $Ax=Bx$ and $A'x=B'x$. Hence $(AB'-A'B)x=AB'x-A'Bx=AA'x-A'Ax=0$.

The result now follows from 1 and 2.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.